2021
DOI: 10.1088/1681-7575/abeb80
|View full text |Cite
|
Sign up to set email alerts
|

Some predictions of a validated physical model of Pt–Rh thermocouple drift above 1200 °C

Abstract: A simple model was recently presented which relates the electromotive force (emf) drift rate of Pt–Rh thermoelements to the vapour pressure of Pt and Rh oxides. The model assumes that the evaporation of these oxides gives rise to a continuously changing concentration of Pt and Rh, at different rates along the length of the wires, which causes a change in the Seebeck coefficient. The model was tested by comparison with high precision measurements under comparable circumstances. By considering various thermocoup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In EMPRESS, a systematic investigation of a number of different Pt-Rh thermocouples showed that the most stable thermocouple consistent with readily available Pt-Rh wire compositions, at least in the temperature range 1324 °C to 1492 °C, is the Pt-40%Rh versus Pt-6%Rh thermocouple [19][20][21]. This is due to the combined effects of thermoelectric drift due to vaporisation of Pt and Rh oxides [34,35,39] A preliminary reference function was also drafted (Figure 2) [19]. In EMPRESS2, to facilitate uptake of the new thermocouple type, NMIs will systematically determine its reference function.…”
Section: Wp2: Low-drift Thermocouplesmentioning
confidence: 99%
“…In EMPRESS, a systematic investigation of a number of different Pt-Rh thermocouples showed that the most stable thermocouple consistent with readily available Pt-Rh wire compositions, at least in the temperature range 1324 °C to 1492 °C, is the Pt-40%Rh versus Pt-6%Rh thermocouple [19][20][21]. This is due to the combined effects of thermoelectric drift due to vaporisation of Pt and Rh oxides [34,35,39] A preliminary reference function was also drafted (Figure 2) [19]. In EMPRESS2, to facilitate uptake of the new thermocouple type, NMIs will systematically determine its reference function.…”
Section: Wp2: Low-drift Thermocouplesmentioning
confidence: 99%